Intertextuality as a Poetic Rewriting Strategy in Pelin Batu’s Self-Translated Poems - Göksenin Abdal (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Intertextual elements contribute to increasing the depth of meaning in literary texts through their associations with present and past texts produced by different authors in the literary world. In Gérard Genette’s terms, they bring together a palimpsest writing, entailing references that are either highlighted or unwittingly removed from literary texts. This study aims to demonstrate how Genette’s concept of intertextuality is reflected in Pelin Batu’s self-translated poems with examples from The Book of Winds / Rüzgarlar Kitabı (2009), The Divan of Lost Things / Kayıp Şeyler Divanı (2015) and It All Began with a Story / Her Şey Bir Hikaye ile Başladı (2018). This study comprises three parts. The first part discusses Genette’s approach to intertextuality in depth, while the second part focuses on the debates regarding translation, self-translation, and intertextuality in translation studies. The third part tries to show how intertextuality has turned into a poetic rewriting strategy in Pelin Batu’s aforementioned works. In conclusion, it has been determined that Pelin Batu, as a Turkish poet, enriches her poems through intertextuality as a rewriting strategy with quotations, allusions and borrowing from various figures of literature, visual arts, art history, philosophy, and science.